Pan-cancer analysis of UGGT1 in human tumors and experimental validation in breast cancer - Xuan Chu; Ligai Zhang; Shiqing Xiang; Yuting Huang (Scientific Reports)
Abstract UDP-glucose: glycoprotein glucosyltransferase 1 (UGGT1), a key component of the endoplasmic reticulum quality control (ERQC) system, has established roles in metabolic/infectious diseases, but its oncogenic potential remains unclear. UGGT1’s expression, genetic alterations, methylation patterns, immune function and interacting genes were evaluated through different bioinformatics databases, and the roles of UGGT1 in breast cancer were validated by in vitro experiments. UGGT1 was significantly overexpressed in most cancers, correlating with advanced stage and poor survival. Variations in its promoter methylation and mutation patterns across cancers were associated with patient outcomes. UGGT1 status (expression/mutation) was significantly associated with immune cell infiltration in the tumor microenvironment. Functional enrichment linked UGGT1 co-expressed genes to cell cycle and nucleic acid metabolism. Critically, UGGT1 knockdown inhibited breast cancer cell proliferation/migration in vitro and downregulated key ER stress sensors (IRE1α, ATF6, PERK). This study establishes UGGT1 as a significant pan-cancer prognostic biomarker and reveals its role in tumor progression, highlighting its potential as a therapeutic target.